The Emergence of the New P.4 Lineage of SARS-CoV-2 With Spike L452R Mutation in Brazil - Bittar, Cíntia; Possebon, Fábio Sossai; Ullmann, Leila Sabrina; Geraldini, Dayla Bott; da Costa, Vivaldo G.; de Almeida, Luiz G. P.; da S. Sanches, Paulo Ricardo; Nascimento-Júnior, Nailton M.; Cilli, Eduardo M.; Artico Banho, Cecília; Campos, Guilherme R. F.; Ferreira, Helena Lage; et al. (Frontiers in Public Health, 2021)
The emergence of several SARS-CoV-2 lineages presenting adaptive mutations is a matter of concern worldwide due to their potential ability to increase transmission and/or evade the immune response. While performing epidemiological and genomic surveillance of SARS-CoV-2 in samples from Porto Ferreira – São Paulo – Brazil, we have identified sequences classified by pangolin as B.1.1.28 harboring Spike L452R mutation, in the RBD region. Phylogenetic analysis revealed that these sequences grouped into a monophyletic branch, with others from Brazil, mainly from the state of São Paulo. The sequences present a set of 15 clade defining amino acid mutations, of which six are located in the Spike protein. It has been proposed to Pango for this to be considered a new lineage and it was designated P.4. In the city of Porto Ferreira, P.4 lineage has been increasing in frequency since it was first detected in March 2021, corresponding to 36.8 % of the samples sequenced in June, the second in prevalence after P.1. Also, it is circulating in 29 cities from the state of São Paulo, and it was recently detected in one sample from the state of Sergipe. Further studies are needed to understand whether P.4 should be considered a Variant of Concern (VOC).